Tel Akko Area H - Brody, Aaron, author.
1 online resource (664 pages)
Keywords: In this volume, Aaron Brody and Michal Artzy offer the first in-depth analysis from excavations at Tel Akko. The most prominent harbor city on the northern coast of the southern Levant, the city was a nexus between the sea routes of the eastern Mediterranean and the overland networks of its hinterland. Stratigraphy, architecture, and material culture from the site’s Area H are presented, along with studies by Jennie Ebeling, Jeffrey Rose, and Edward Maher on stone artifacts and animal bones from burials. The volume presents Middle Bronze IIA rampart materials and MB IIB-IIC burials; transitional end of Late Bronze-beginning of Iron I finds; and southern Phoenician ceramics. The Studies in the Archaeology and History of the Levant series publishes volumes from the Harvard Museum of the Ancient Near East. Other series offered by Brill that publish volumes from the Museum include Harvard Semitic Studies and Harvard Semitic Monographs, Link .